การเพิ่มมูลค่าขององค์กรจากบรรษัทภิบาล: Enhancing Enterprise Value through Corporate Governance - กิตตินรรัตน์ จักรพันธ์ (Journal of Applied Economics and Management Strategy, 2018)
บรรษัทภิบาล (Corporate Governance) กำลังเป็นประเด็นที่ได้รับการกล่าวถึงและได้รับความสำคัญมากขึ้นทั้งจากภาครัฐและภาคเอกชน โดยเฉพาะในสถานการณ์ปัจจุบันที่มีเหตุการณ์ต่างๆ ที่เกิดขึ้นในเรื่องของการทุจริต การคอรัปชั่น การจงใจบิดเบือนข้อมูลข่าวสาร หรือการบริหารจัดการที่ผิดพลาดของบริษัทขนาดใหญ่เกิดขึ้น และได้รับการเปิดเผยออกมาเป็นระยะ ซึ่งส่งผลให้เกิดการล้มละลายของธุรกิจ คิดเป็นมูลค่ามหาศาล อีกทั้งยังไม่มีสิ่งที่สามารถบ่งบอกได้ว่าเหตุการณ์ในลักษณะดังกล่าวจะไม่เกิดขึ้น ในอนาคตอันใกล้ ยิ่งเป็นสิ่งที่ย้ำให้เห็นความสำคัญของบรรษัทภิบาลมากขึ้น ดังนั้นบทความนี้จึงมุ่งอธิบายถึงความหมาย และความสำคัญของการมีบรรษัทภิบาลกับการเพิ่มมูลค่ากิจการเพื่อเป็นประโยชน์ในการนำไปสู่การเสริมสร้างบรรษัทภิบาล และการเพิ่มมูลค่าทางธุรกิจขององค์กรในอนาคต Corporate Governance is the issue that has now received widespread attention and focus from both the public and private sectors. This is especially true given the ongoing concerns over corruption, fraud, intentional misrepresentation of information, and mismanagement of large companies resulted in the bankruptcy of the businesses and losses of tremendous value. There are no guarantee that these events will not happen again in the near future. Society now gives more emphasis on the importance of corporate governance. Therefore, this article aims to explain the meaning and importance of corporate governance in increasing enterprise value which would create better understanding on the benefit of strengthening corporate governance and increasing the business value of enterprise in the future.